The significant contribution of Caliphs in the efflorescence of Muslim librarianship: a historical account - Ahmad H.Osman, Rahmah; Mahadi, Mawloud (IIUM Press, International Islamic University Malaysia, 2018)
Muslim education started as early as the first revelation received by Prophet Muhammad . The quest for knowledge is an obligation on all Muslims in Islam. Hence, it has been the mission and passion of all the Muslim rulers throughout the Islamic civilization. History has witnessed the quest and mission of the Umayyads and Abbasids caliphs and many others in the acquiring of books, establishment of institutions, and the acquisition and dissemination of knowledge. This paper investigates the beginning of Muslim librarianship and development of the book industry across the centuries. It also examines the evolution of Muslim bibliophilism and the establishment of libraries that would eventually become cultural institutions. In addition, the current paper attempts to understand the significant role of caliphs who devoted their fortunes for Muslim education. The paper follows a qualitative research founded on historical and descriptive approaches, through which the data was collected and interpreted objectively.